Re-examination of the Khar khoroot inscription (Studia Archaeologica, 2024)
The inscriptions of Khar Khoroot, Bayanbürd Bag, Buutsagaan Sum, Bayankhongor Province, were re-examined. A few characters and letters were inadvertently copied. There is a single line of inscription in the Khar Khoroot that says,  yätmis apa on bašï bitidim ~ I, the corporal, wrote for Yetmish Apa”. Except for Khar Khoroot, none of the Mongolian runic monuments have intentionally drawn boundaries. The inscription on Khar Khoroot is unique in this regard. Upon the demise of a nobleman named Yätmis Apa, an inscription was crafted in his honor. The framing of the inscription might serve as a symbolic indication of its intended purpose for a funeral. Depicting deceased individuals through the use of frames and fences is a prevalent practice in human societies, serving as a universal emblem and symbol throughout cultures. Put simply, Yetmish Apa, who died while traveling, was unable to construct a sacrificial complex due to lack of chance or time. As a result, they were burned, and a commemorative inscription was made. The absence of any other stamp associated with the Turkic and Uighur periods on the Khar Khoroot rock indicates that the scribes had a brief presence and only inscribed on specific occasions. Chronologically, it is clear that the Khar Khoroot inscription belongs to the Uighur period.Хар хороотын бичээсийг нягтлахадТовчлол. Баянхонгор аймгийн Бууцагаан сумын Баянбүрд багийн нутаг Хар хороотын бичээсийг дахин нягталлаа. Зарим үсэг тэмдэгтийг ташаарч хуулснаас судалгаа мадагтай болсон байна. Хар хороотод m}thi\vnoaPSmtJ ~ yätmis apa on bašï bitidim ~ Йэтмиш апад [зориулж] аравтын дарга бичив би гэсэн ганц мөр бичээс байх ажээ. Бичээсийг тусгайлан хүрээ татаж бичсэн байх ба Монголын руни бичгийн бага дурсгалуудаас зорилготойгоор хүрээ татаж бичсэн бичээс одоогоор Хар хороотоос өөр байхгүй байна. aPSmtJ yätmis apa гэх язгууртан тэнгэрт хальсанд, түүнд зориулж үйлдээд хойлго, оршуулгад зориулсан болохыг хүрээгээр төлөөлүүлсэн байх магадлалтай. Нас барсныг хүрээ, хашлагаар төлөөлүүлэх нь хүн төрөлхтний соёлын нийтлэг хэв шинж бөгөөд аль ч соёлд түгээмэл байдаг тэмдэг, тэмдэглэгээ билээ. Өөрөөр хэлбэл, аян замын зуур тэнгэрт хальсан Йэтмиш апа-д тахилын онгон байгуулах боломж, цаг зав байсангүйд чандарлан оршуулаад аравтын дарга бичээс үйлдсэн байж болох юм. Хар хороотын хаданд Түрэг, Уйгурын үед холбогдох өөр тамга тэмдэг ганц ч байхгүй байгаа нь бичээс үйлдэгчид маш богино хугацаагаар түр буудалласан, мөн онцгой тохиолдлоор бичээс бичиж үйлдсэн болохыг харуулна. Он цагийн хувьд Хар хороотын бичээс Уйгурын үед холбогдох нь тодорхой байна.Түлхүүр үг. Баянхонгор аймаг, Бууцагаан сум, Хар хороот, руни бичиг, тамга